Prenatal environmental tobacco smoke exposure increases allergic asthma risk with methylation changes in mice. (25th May 2017) - Christensen, Sonja; Jaffar, Zeina; Cole, Elizabeth; Porter, Virginia; Ferrini, Maria; Postma, Britten; Pinkerton, Kent E.; Yang, Mihi; Kim, Yang Jee; Montrose, Luke; Roberts, Kevan; Holian, Andrij; et al.
Abstract : Allergic asthma remains an inadequately understood disease. In utero exposure to environmental tobacco smoke (ETS) has been identified as an environmental exposure that can increase an individual's asthma risk. To improve our understanding of asthma onset and development, we examined the effect of in utero ETS exposure on allergic disease susceptibility in an asthmatic phenotype using a house dust mite (HDM) allergen‐induced murine model. Pregnant C57BL/6 mice were exposed to either filtered air or ETS during gestation, and their offspring were further exposed to HDM at 6–7 weeks old to induce allergic inflammation. Methylation in the promoter regions of allergic inflammation‐related genes and genomic DNA was quantified. Exposure to HDM resulted in the onset of allergic lung inflammation, with an increased presence of inflammatory cells, Th2 cytokines (IL‐4, IL‐5, and IL‐13), and airway remodeling. These asthmatic phenotypes were significantly enhanced when the mice had been exposed to in utero ETS. Furthermore, prenatal ETS exposure and subsequent HDM (ETS/HDM)‐induced asthmatic phenotypes agree with methylation changes in the selected asthma‐related genes, including IL‐4, IL‐5, IL‐13, INF ‐γ, and FOXP3 . Global DNA methylation was significantly lower in ETS/HDM‐exposed mice than that of controls, which coincides with the results observed in lung, spleen, and blood DNAs. Prenatal ETS exposure resulted in a severe increase in allergic inflammatory responses after an HDM challenge, with corresponding methylation changes. Prenatal ETS exposure may influence developmental plasticity and result in altered epigenetic programming, leading to an increased susceptibility to asthma. Environ. Mol. Mutagen. 58:423–433, 2017. © 2017 Wiley Periodicals, Inc.